Improvement Thermal Efficiency of Al-Rumaila Gas Turbine Power Plant in Basrah by Upstream Inlet Air Cooling System - Ojimi, Ammar Ali (Basrah Journal for Engineering Sciences, 2025)
The efficiency of gas turbine units is highly affected by the variation of ambient temperature. Increasing the ambient temperature decreasing the efficiency of gas turbine. Cooling the inlet air to the compressor of the gas turbine units is an essential and economical technique for improving its efficiency. Al-Rumaila gas turbine power plant was located in Basrah city, Iraq, which is characterized by its hot climates for more than six months during the year. A novel upstream inlet air cooling system was applied and tested for Rumaila gas turbine power plant. This article represents a thermo-economic evaluation of applying upstream inlet air cooling system. The analysis is based on the test results for operating single unit of Rumaila gas turbine power plant using upstream inlet air system for cooling. The test was performed during July of 2019 for 90 minutes of operation period with ambient temperature of 45 °C. The evaluation analysis shows that, the power output increased from 217.71 MW to 250.11 MW during the period test with percentage increase in power by 15%. This increase in power output led to net economic gains is approximately 1000 $/h.